A national survey of obstetric early warning systems in the United Kingdom: five years on. (7th May 2014) - Isaacs, R. A.; Wee, M. Y. K.; Bick, D. E.; Beake, S.; Sheppard, Z. A.; Thomas, S.; Hundley, V.; Smith, G. B.; van Teijlingen, E.; Thomas, P. W.; Members of the Modified Obstetric Early Warning Systems (MObs) Research Group
Summary The Confidential Enquiries into Maternal Deaths in the UK have recommended obstetric early warning systems for early identification of clinical deterioration to reduce maternal morbidity and mortality. This survey explored early warning systems currently used by maternity units in the UK. An electronic questionnaire was sent to all 205 lead obstetric anaesthetists under the auspices of the Obstetric Anaesthetists' Association, generating 130 (63%) responses. All respondents reported use of an obstetric early warning system, compared with 19% in a similar survey in 2007. Respondents agreed that the six most important physiological parameters to record were respiratory rate, heart rate, temperature, systolic and diastolic blood pressure and oxygen saturation. One hundred and eighteen (91%) lead anaesthetists agreed that early warning systems helped to prevent obstetric morbidity. Staffing pressures were perceived as the greatest barrier to their use, and improved audit, education and training for healthcare professionals were identified as priority areas.